Aerobic Exercise Berpengaruh terhadap Peak Expiratory Flow (PEF) pada Mahasiswa - Eka Kurnia Sari; Nurul Aini Rahmawati; Ali Multazam (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Sedentary Lifestyle has an impact on decreased respiratory muscle strength, decreased lung expiratory function and is at risk of causing other diseases. Lack of activities such as exercise can affect the health of the body and decrease lung function, the disturbed lungs will experience a decrease in lung recoil elasticity so that the absorption of airflow is not optimal and causes disturbances in expiration and inspiration, especially in PEF (Peak Expiratory Flow) which is the maximum airflow velocity achieved during forced expiration. PEF that drops below 80% indicates lung impairment. Low PEF can cause dypsnea, wheezing, shortness of breath. The purpose of this study was to determine the effectiveness of aerobic exercise on PEF increase. This research method used pre-experimental one-group pretest-posttest design. With undergraduate students of PhysiotherapyMuhammadiyah Malang as respondents who meet the inclusion and exclusion criteria. Measurement of pretest and posttest data using spirometer. Post test was conducted after jogging for 4 weeks and 12 sessions. The results of the Paired Sample Test showed that Aerobic Exercise had an effect on increasing PEF, namely (p = 0.000) p<0.05